2012
DOI: 10.1007/s00253-012-4484-3
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan hydrolases-potential weapons against Staphylococcus aureus

Abstract: Bacteria of the genus Staphylococcus are common pathogens responsible for a broad spectrum of human and animal infections and belong to the most important etiological factors causing food poisoning. Because of rapid increase in the prevalence of isolation of staphylococci resistant to many antibiotics, there is an urgent need for the development of new alternative chemotherapeutics. A number of studies have recently demonstrated the strong potential of peptidoglycan hydrolases (PHs) to control and treat infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
85
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 142 publications
4
85
0
1
Order By: Relevance
“…In another study, 42% isolates were found to be biofilm producer (Dziekiewicz -Mrugasiewicz et al, 2008). Szweda et al (2012) found 57% positive isolates by CRA method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, 42% isolates were found to be biofilm producer (Dziekiewicz -Mrugasiewicz et al, 2008). Szweda et al (2012) found 57% positive isolates by CRA method.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the previous reports on S. aureus by Cucarella et al (2001) who found only 5% isolates positive for bap gene. Szweda et al (2012) did not report bap gene in any of isolates in his study in Poland. Similar, results were found in S. aureus isolates of different origin, such as human, sheep, goat, bovine, pig, poultry, horse and rabbit (Vancraeynest et al, 2004;Nitzsche et al, 2007;Vautor et al, 2008;Melchior et al, 2009), Vantor andcowoekers (2008), hypothesized that the bap gene has not spread among the S. aureus isolates of animal and human origin and its prevalence is very low.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to wine-related microorganisms, bacteria of the genus Staphylococcus were lysed by the culture supernatant. As many staphylococci are known as human pathogens, the lytic enzymes of S. albidoflavus B 578 may also be of some medical interest [27]- [30].…”
Section: Discussionmentioning
confidence: 99%
“…Пептидоглика-ны, которые представляют собой гетерополимеры N-ацетил-D-глюкозамина и N-ацетилмурамовой кислоты, соединенные β-1,4-гликозидными связя-ми, являются основными лигандами NLR: NLRC1/ NOD1 и NLRC2/NOD2 [27,88].…”
Section: Nod-подобные рецепторыunclassified